Effect of nanoparticles on the growth of okra cultivated in soil affected by rocky desertification - Jiyue Wang; Xiaojian Tian; Shuai Wei; Xiuhuan Meng; Nian Chen; Denghong Shi; Chenggang Liang (Scientific Reports)
Abstract This study investigated the influence of various nanoparticles (NPs), including carbon-based NPs, Al2O3-NPs, SiO2-NPs, and TiO2-NPs, on the growth and physiology of okra plants cultivated in soil impacted by rocky desertification. The morphological characteristics, photosynthetic parameters, antioxidant capacity, nutrient uptake of the okra plants, and available nutrient content in the soil were evaluated. The results demonstrated a significant improvement in the growth, photosynthetic properties, chlorophyll content, and activities of antioxidant enzymes (catalase, peroxidase, and superoxide dismutase) in the okra plants treated with NPs compared to the control. Additionally, the NP-treated plants exhibited enhanced total nitrogen content, and hydrolysis nitrogen content in soil was also significantly increased, indicating improved nitrogen uptake. Notably, TiO2-NPs demonstrated the most pronounced effects on plant growth and photosynthetic characteristics, while TiO2-NPs and SiO2-NPs showed higher antioxidant enhancement compared to other NPs. These findings suggest the potential of nanoparticles as a promising agricultural solution to address challenges in regions like Guizhou Province, China.